Acidification and sulfide formation control during reductive dechlorination of 1, 2-dichloroethane in groundwater: Effectiveness and mechanistic study. (October 2016) - Wang, S.Y.; Chen, S.C.; Lin, Y.C.; Kuo, Y.C.; Chen, J.Y.; Kao, C.M.
Abstract: To enhance the reductive dechlorination of 1, 2-dichloroethane (DCA) in groundwater, substrate injection may be required. However, substrate biodegradation causes groundwater acidification and sulfide production, which inhibits the bacteria responsible for DCA dechlorination and results in an odor problem. In the microcosm study, the effectiveness of the addition of ferrous sulfate (FS), desulfurization slag (DS), and nanoscale zero-valent iron (nZVI) on acidification and sulfide control was studied during reductive dechlorination of DCA, and the emulsified substrate (ES) was used as the substrate. Up to 94% of the sulfide was removed with FS and DS addition (0.25 wt%) (initial DCA concentration = 13.5 mg/L). FS and DS amendments resulted in the formation of a metal sulfide, which reduced the hydrogen sulfide concentration as well as the subsequent odor problem. Approximately 96% of the DCA was degraded under reductive dechlorination with nZVI or DS addition using ES as the substrate. In microcosms with nZVI or DS addition, the sulfide concentration was reduced to less than 15 μg/L. Acidification can be controlled via hydroxide ions production after nZVI oxidation and reaction of free CaO (released from DS) with water, which enhanced DCA dechlorination. The quantitative polymerase chain reaction results confirmed that the microcosms with nZVI added had the highest Dehalococcoides population (up to 2.5 × 10 8 gene copies/g soil) due to effective acidification control. The α-elimination mechanism was the main abiotic process, and reductive dechlorination dominated by Dehalococcides was the biotic mechanism that resulted in DCA removal. More than 22 bacterial species were detected, and dechlorinating bacteria existed in soils under alkaline and acidic conditions. Highlights: nZVI can enhance DCA dechlorination without sulfide accumulation and acidification. DS can prevent acidification, remove sulfide, and enhance DCA removal. Ferrous sulfate caused reducing capacity drop, which resulted in decreased DCA removal. DS and nZVI favored Dehalococcoides growth due to neutralized and reduced environment. Abiotic α-elimination and biotic dechlorination were mechanisms for DCA removal.